2016
DOI: 10.1152/ajpendo.00434.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovariectomy and intrinsic aerobic capacity on tissue-specific insulin sensitivity

Abstract: High-capacity running (HCR) rats are protected against the early (i.e., ∼ 11 wk postsurgery) development of ovariectomy (OVX)-induced insulin resistance (IR) compared with low-capacity running (LCR) rats. The purpose of this study was to utilize the hyperinsulinemic euglycemic clamp to determine whether 1) HCR rats remain protected from OVX-induced IR when the time following OVX is extended to 27 wk and 2) tissue-specific glucose uptake differences are responsible for the protection in HCR rats under sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…We recently demonstrated that LCR rats are more susceptible to ovariectomy-associated metabolic dysfunction (25, 40) and the combination of ovariectomy plus HFD (24) compared to HCR. EX is a highly effective treatment to reverse metabolic dysfunction including insulin resistance via enhancing aerobic capacity (6, 17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that LCR rats are more susceptible to ovariectomy-associated metabolic dysfunction (25, 40) and the combination of ovariectomy plus HFD (24) compared to HCR. EX is a highly effective treatment to reverse metabolic dysfunction including insulin resistance via enhancing aerobic capacity (6, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy surgeries were conducted as previously described (25). All rats were anesthetized by inhaled isofluorane at 2% during surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recently demonstrated a strong impact of ovarian hormones on metabolic function (i.e., tissue-specific insulin sensitivity) independent of intrinsic aerobic capacity level [41]. Among ovarian hormones, circulating E 2 is the critical mediator of physical activity in female animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies continue to match findings in this model to those in humans. LCR rats have now been shown to be more susceptible to a variety of other conditions that are also linked to low aerobic capacity in humans (16, 26, 39). …”
Section: Introductionmentioning
confidence: 99%